2020
DOI: 10.1123/tsp.2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

The Highs and the Lows—Exploring the Nature of Optimally Impactful Development Experiences on the Talent Pathway

Abstract: There appears to be general agreement that interaction with significant challenge should be a central feature of the development pathways for future high performers. There is, however, far less clarity about how such programs should be designed and delivered against core psychological principles. Accordingly, the purpose of this paper is to offer guidelines for talent development practitioners seeking to offer athletes the opportunity to maximize their growth and development. The authors propose that genuinely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 81 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…PJDM—Martindale and Collins, 2013 ). This is especially so as the correlates of PS are complex and not always wholly positive (Taylor and Collins, 2020 ). As such, we repeat a recent call for an increased level of criticality, especially for those seeking to develop evidence-informed practice (Stoszkowski et al, 2020 ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…PJDM—Martindale and Collins, 2013 ). This is especially so as the correlates of PS are complex and not always wholly positive (Taylor and Collins, 2020 ). As such, we repeat a recent call for an increased level of criticality, especially for those seeking to develop evidence-informed practice (Stoszkowski et al, 2020 ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Despite historic characterisations of the aims and objectives of youth sport coaching being very much a short-term endeavour, with a focus on maximising short-term enjoyment, this data clearly suggests that there is a need to focus just as much on the vertical as the horizontal ( Taylor and Collins, 2020 ). Illustrative of the complexity, it is clear that some players needed periods of carefully managed challenge-full and less enjoyable activity to support their long-term participation (cf.…”
Section: Applied Implicationsmentioning
confidence: 88%
“…At the micro level, the coach should look to nest their moment to moment and short-term coaching decisions within these longer-term agendas (e.g., motivational status of participant). Thus, to navigate the complexities of development, there is a need for a professional judgment and decision making (PJDM) approach, with the coach ideally weighing up the tentative balance of short- and long-term needs ( Taylor and Collins, 2020 ). In turn, the coach needs to carefully consider the relative ranking of these needs, ideally working toward a long-term nested agenda ( Abraham and Collins, 2011b ).…”
Section: Introductionmentioning
confidence: 99%
“…Key differences between these positions notwithstanding, it appears that performers who bring a variety of psycho-behavioral resources to challenging periods will be more likely to cope with and learn from their experience [42]. In this regard, recent investigations have suggested that challenge-filled sporting pathways are an essential feature of developmental journeys [43]. Further, it appears that sporting 'traumas' and/or challenging experiences, rather than being directly causative of 'psychological growth', instead act to test, prove and encourage previously developed psychological skills [42].…”
Section: Mechanismsmentioning
confidence: 99%
“…Reflecting these complexities, and beyond establishing RAEs and consequently advantage reversals in different contexts, there is a need to understand the mechanisms at play [23]. This is especially the case for the applied practitioner or policy maker who needs to make decisions regarding sporting systems, placing the individual performer's experience as a primary concern [43]. Accordingly, this paper aimed to (a) generate a deeper understanding of the lived experience of the RAE in TD systems across groups of more and less successful athletes, (b) compare the experience of early and late born players, and (c) explore the mechanisms influencing individual experiences.…”
Section: Mechanismsmentioning
confidence: 99%